Management of Unresectable T4b Esophageal Cancer: Practice Patterns and Outcomes From the National Cancer Data Base. (February 2019) - Cushman, Taylor R.; Shaaban, Sherif G.; Moreno, Amy C.; Lin, Chi; Verma, Vivek
Abstract : Purpose: Patients with unresectable cT4b esophageal cancer (EC) are rare and largely excluded from prospective trials. As a result, current treatment recommendations are based on limited evidence. This study sought to evaluate national practice patterns and outcomes for this population and evaluated 3 primary cohorts: patients receiving chemotherapy (CT) with or without subtherapeutic radiotherapy (RT), definitive chemoradiotherapy (CRT), or CT with or without RT followed by definitive surgery. Materials and Methods: The National Cancer Data Base was queried for cT4b Nany M0 EC. Exclusion criteria were patients with unspecified staging, palliative treatment, improper, or no histologic confirmation, or lack of CT. Multivariable logistic regression determined factors predictive of receiving surgical therapy. Kaplan-Meier analysis evaluated overall survival (OS), and Cox proportional hazards modeling determined variables associated with OS. Results: Altogether, 519 patients met inclusion criteria; 195 (38%) underwent CT, 291 (56%) underwent definitive CRT, and 33 (6%) underwent surgical-based therapy. Surgery was more likely performed in patients residing in rural areas, living farther from the treating facility, and N1 status ( P <0.05 for all). Median OS in the respective cohorts were 6.0, 12.7, and 43.9 months ( P <0.001). On multivariate Cox proportional hazards modeling, among others, nonsurgical treatment was associated with poorer OS ( P <0.05 for both). Conclusions: In the largest study to date evaluating patterns of care for cT4b EC, as compared with CT alone, addition of definitive RT was associated with higher OS. Although causation is clearly not implied, well-selected responders to CT and/or RT may be able to undergo resection and numerically prolonged survival, but patient selection remains paramount.